2015
DOI: 10.1007/s12147-015-9134-5
|View full text |Cite
|
Sign up to set email alerts
|

Is Everybody Doing It? Perceptions and Misperceptions of Sexual Behavior in the College Freshman Population

Abstract: Descriptive and injunctive norms have been shown to influence people's perceptions of what actions are considered appropriate, but they are frequently based on misperceptions. Men and women often hold varying perceptions with regards to sexual attitudes and behaviors. One hundred fifty-six heterosexual freshman women and 135 heterosexual freshman men were surveyed about their own sexually permissive attitudes and behaviors and their perceptions of their best friend's and the average same-sex freshman's attitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 48 publications
(88 reference statements)
0
8
0
Order By: Relevance
“…In fact, we scrutinised the changing determinants of a selected pool of sexual behaviour which past research has already shown to be crucial and, according to our data, changed more significantly over time than others. These are the number of males watching pornography (Goodson et al, 2001;Braitwaite et al, 2015;for Italy, Romito and Beltramini, 2011;Cuccì et al, 2017;Scarcelli and Stella, 2019), the number of females who have had homosexual experiences (Goode and Haber, 1977;Kuperberg and Walker, 2018), the number of males betraying their partner (Allen and Baucom, 2006;McAnulty and Brineman, 2007;Norona et al, 2015), and having three or more sexual partners for females (Wiederman, 1997;Brown and Sinclair, 1999;Eisenberg, 2001;Zelin et al, 2015;Mitchell et al, 2019). As each of these behaviour has its own specificity, it is not possible to discuss in-depth every main determinant of these four sexual behaviours in a single study.…”
Section: Factors Affecting Changing Sexual Behavioursmentioning
confidence: 99%
“…In fact, we scrutinised the changing determinants of a selected pool of sexual behaviour which past research has already shown to be crucial and, according to our data, changed more significantly over time than others. These are the number of males watching pornography (Goodson et al, 2001;Braitwaite et al, 2015;for Italy, Romito and Beltramini, 2011;Cuccì et al, 2017;Scarcelli and Stella, 2019), the number of females who have had homosexual experiences (Goode and Haber, 1977;Kuperberg and Walker, 2018), the number of males betraying their partner (Allen and Baucom, 2006;McAnulty and Brineman, 2007;Norona et al, 2015), and having three or more sexual partners for females (Wiederman, 1997;Brown and Sinclair, 1999;Eisenberg, 2001;Zelin et al, 2015;Mitchell et al, 2019). As each of these behaviour has its own specificity, it is not possible to discuss in-depth every main determinant of these four sexual behaviours in a single study.…”
Section: Factors Affecting Changing Sexual Behavioursmentioning
confidence: 99%
“…Researchers studying college students using a three-type differentiation scale (self, best friend, and "typical other") indicated that freshmen women perceive a "typical other" woman student as having significantly more sex/sexual activity than her best friend and herself (Zelin, Erchull, & Houston, 2015). Thus, in the context of bystander behavior, a woman who sees a friend or acquaintance in a pre-assault situation may think, "I wouldn't want this to happen to me, and my best friend probably wouldn't either, so I should intervene."…”
Section: Studymentioning
confidence: 99%
“…Moreover, in our final model, sociosexual attitudes in high school showed a direct prospective association with sexual aggression in Year 2 of college (but not in Year 1), suggesting the potential utility of targeting misperceived attitudes related to casual sex (Zelin et al, 2015) in sexual-assault prevention programs. This finding extends prior empirical work that is largely cross-sectional in nature (Davis et al, 2018) and provides further support for impersonal sex as a central mechanism in the prevailing theoretical model of sexual aggression (Malamuth & Hald, 2017).…”
Section: Discussionmentioning
confidence: 85%
“…The selection effect for sociosexual attitudes, but not sociosexual behaviors, underscores the importance of distinguishing attitudinal and behavioral aspects of sociosexuality (Corbin et al, 2016; Penke & Asendorpf, 2008; Webster & Bryan, 2007). Research indicates that college students overestimate their peers’ sociosexual attitudes (Zelin et al, 2015), those who endorse sociosexual attitudes show greater overestimation than their peers (Zelin et al, 2015), and one’s own attitudes are related to the perceived attitudes of peers (Lewis et al, 2014). Thus, it may be useful to target misperceived injunctive norms for casual sexual behavior with normative feedback, particularly among those interested in joining a fraternity.…”
Section: Discussionmentioning
confidence: 99%